2010
DOI: 10.1186/1471-2229-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expressed sequence tags from a single wheat cultivar facilitates interpretation of tandem mass spectrometry data and discrimination of gamma gliadin proteins that may play different functional roles in flour

Abstract: BackgroundThe gamma gliadins are a complex group of proteins that together with other gluten proteins determine the functional properties of wheat flour. The proteins have unusually high levels of glutamine and proline and contain large regions of repetitive sequences. While most gamma gliadins are monomeric proteins containing eight conserved cysteine residues, some contain an additional cysteine residue that enables them to be linked with other gluten proteins into large polymers that are critical for flour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 30 publications
2
41
1
Order By: Relevance
“…Hajheidari et al (2007) detected changes in 121 spots with drought, but only 57 were identified. In addition, 36 minor spots that changed with fertilizer were not identified in the Altenbach et al (2011) study. Some proteins are difficult to identify by MS because they are of very low abundance.…”
Section: Proteomic Analysis Of Non-gluten Proteinscontrasting
confidence: 51%
See 2 more Smart Citations
“…Hajheidari et al (2007) detected changes in 121 spots with drought, but only 57 were identified. In addition, 36 minor spots that changed with fertilizer were not identified in the Altenbach et al (2011) study. Some proteins are difficult to identify by MS because they are of very low abundance.…”
Section: Proteomic Analysis Of Non-gluten Proteinscontrasting
confidence: 51%
“…Yang et al (2011) applied a water deficit from anthesis and Hajheidari et al (2007) limited the amount of water in field grown wheat from the booting stage throughout grain development. Grove et al (2009) examined proteins that changed in response to fertilization with sulfur (S) while Dupont et al (2006a,b) and Altenbach et al (2011) focused on proteins that changed in response to nitrogen (N) fertilization. Most studies assessed protein levels either late in development or at maturity.…”
Section: Proteomics Approaches For Studying Effects Of Environment Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular cloning and sequencing of these genes are helpful for better understanding the relationships of their structures and functions, and will provide vital information on gene evolution (Guo et al, 2010). In the Triticeae, γ-gliadin genes have been cloned from the genus Triticum (Anderson et al, 2001;Qi et al, 2009;Altenbach et al, 2010), Aegilops (Qi et al, 2009;Huang et al, 2010), Thinopyrum , and Crithopsis (Guo et al, 2010). However, no γ-gliadin genes have been cloned from the genus Dasypyrum.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 13 unique γ-gliadin encoding genes have been reported to be present in the Chinese Spring wheat genome, and 11 of them are active according to the ESTs and NGS analysis (Anderson et al 2013). In the cultivar Butte 86, nine γ-gliadin genes 5 encoding full length proteins were identified by EST analysis (Altenbach et al 2010).…”
mentioning
confidence: 99%